Anti‐adiposity and lipid‐lowering effects of schisandrol A in diet‐induced obese mice. Issue 12 (4th November 2022) - Kim, Sang Ryong; Park, Hyo Jin; Jung, Un Ju
Abstract: Lignan schisandrol A (SolA) is known to have antioxidant and anti‐inflammatory effects. However, the impact of SolA on obesity is poorly understood. To test the hypothesis that SolA has anti‐obesity effects, C57BL/6J mice were fed a high‐fat diet with or without SolA (0.006%, w/w) for 16 weeks. SolA decreased visceral fat mass (10%) by increasing energy expenditure and upregulating white adipose tissue thermogenic genes mRNA expression. Furthermore, SolA upregulated adipose Lpl mRNA expression and decreased plasma free fatty acid (FFA), triglyceride (TG), apolipoprotein (apo) B, aspartate aminotransferase levels and TG/HDL‐cholesterol and apoB/apoA1 ratios as well as hepatic lipid droplets. Increased hepatic β‐oxidation and fecal FFA and TG levels were observed in the SolA‐supplemented mice, suggesting an association of its lipid‐lowering effect with increased hepatic β‐oxidation, fecal fat excretion and adipose Lpl . Conclusionally, this study provides evidence on the protective effects of SolA against adiposity, dyslipidemia and nonalcoholic fatty liver disease in obese mice. Abstract : This study examined the anti‐obesity effect of schisandrol A (SolA), a lignan derived from the fruit of Schisandra chinensis (Turcz.) Baill., in obese mice that were fed a high‐fat diet. SolA supplementation reduced visceral adiposity by increasing energy expenditure and mRNA expression of thermogenic genes in white adipose tissue (WAT). Moreover, SolA decreased hepatic lipogenic enzyme activity and increased hepatic fatty acid oxidation, fecal lipid excretion and WAT lipoprotein lipase mRNA expression, which could confer protection from dyslipidemia and hepatic steatosis.